Assessing the local people's preferences for different traits of native medicinal trees in Northern Sri LanKa - Manoharan, Sarathanjali; Shrestha, Rajendra Prasad; Tsusaka, Takuji W.; Szabo, Sylvia Maria; Joint Japan/World Bank GraduateScholarship Program (JJ/WBGSP); Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2020)
Worldwide, native tree-based systems are disappearing due to anthropogenic causes including climate change. Sri Lanka is not exempt from this. Sri Lanka's Northern, natural forests are threatened by post conflict development and resettlement activities despite initiatives undertaken to conserve them. Furthermore, the Northern region which has trees of medicinal value, lacks relevant scientific data which is vital for conservation. Therefore, this study intended to understand the preferences of native medicinal trees in farm lands by inventorying all the trees of medicinal value, native to the province. Among them, important tree traits preferred by the people for planting, and the characteristics underlying these preferences were explored through economic valuation. The population targeted by the study is people facing high deforestation over the past three years in the Northern Province of Sri Lanka. 219 households belonging to 13 village administration units were studied. Study was designed with discrete choice experiments. Pro bit and conditional logit regression models were used to analyse the data. Result of the study provided a use based native medicinal tree inventory of the province. The higher the cultural significance and uses, the better the trees are found to be known to people. Trees of economic, ecological significance were found to be supoorting them to cope with distress. Timber value trees were more prone to corruption. Overall the communities have placed higher values on the identified traits "high value for NTFPs", "high timber value","multipurpose", "spiritual use" and "time taken to reap benefits" and the values were 220 USD, 139 USD, 100 USD, 56 USD, 35 USD respectively. Characteristics such gender, age, membership in village based societies, income, land tenure, accessibility to forest and planting site, access to basic facilities, negative beliefs, community support, support to cope drought and floods, goverance of tree based resources were found to be influencing tree planting decisions. This study is the first of its kind in Sri Lanka and it investigated planting decisions at trait level. The results could support conservation decision making with a focus on engaging local communities to create win-win solutions and academics for future research. It laid the foundation to explore the forgotten benefits of native medicinal trees in the region which would enable their sustainable use, management and protection while ensuring income generation opportunities to the conflict affected communities to sustain their lives. Thereby it could indirectly contribute towards agenda 2030.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2020
Keywords: Native plant gardens -- Sri Lanka; Medicinal plants -- Sri Lanka